Thorium(IV) and Uranium(IV) Complexes with 2,6-Dipicolinoylbis(N,N-diethylthiourea) Ligands - Christelle Njiki Noufele; Juliane März; Ulrich Abram (Molbank)
The reaction of thorium nitrate hydrate with 2,6-dipicolinoylbis(N,N-diethylthiourea), H2Lpic, results in the hydrolysis of the organic ligand and the formation of [Th(2,6-dipicolinolate)2(H2O)4] (1). Hydrolysis can be avoided by the use of [ThCl4(DME)2] (DME = 1,2-dimethoxyethane) as the starting material and the exclusion of water. The product, [Th(Lpic)3]2− (2), crystallizes as diammonium salt in form of yellow crystals in moderate yields. The thorium ion in the complex is nine-coordinate by the central O,N,O donor atoms of three deprotonated {Lpic}2− ligands. The sulfur atoms of the ligands do not bind to the actinide ion, but establish hydrogen bonds to the ammonium counter ions. A similar coordination sphere is also observed in the uranium(IV) complex [UAu2(Lpic)3}] (3), which was obtained from a reaction between H2Lpic, [U2I6(1,4-dioxane)3] and [AuCl(tht)] (tht = tetrahydrothiophene) in the presence of triethylamine. Charge compensation is established by the linear coordination of two Au+ ions between each two sulfur atoms of the ligands. The products have been studied by X-ray diffraction and IR spectroscopy. The actinide ions in both {Lpic}2− complexes have coordination number nine, but establish slightly different coordination spheres.